Basic design of a cooling system for nylon 6, 6 process - Silaipillayarputhur Ph. D, Karthik; Al Mulhim, Nasser; Al Mulhim, Abdullah; Arfaj, Mohammed; Al Naim, Ahmed (International Journal of Engineering and Technology, 2018)
The project concentrates on the basic design of a cooling system for rapidly cooling nylon 6, 6 polymer fibers using cold air. The ambient air after pre-treatment in the air-washer is available at 72°F all year round. Based on the company’s throughput, it is required to supply (quench) air at 58°F. Nylon 6, 6 polymer after thorough polymerization is distributed through 16 quench cabinets and each quench cabinet requires approximately 530 ft3/min (cubic feet per minute, CFM) of air. The project concentrates on the basic design of a cooling system wherein air at the required mass flow rate is supplied at 58°F for the quenching process. A basic design of the refrigeration cycle and heat exchangers were considered in this work. In the development of the basic design for heat exchanger, performance charts were developed. Performance charts describe the performance of the heat exchanger in terms of fundamental dimensionless parameters. Using performance charts it was clearly seen that increasing the number of transfer units (NTU) doesn’t necessarily increase the rate of heat transfer. Increasing the NTU beyond an optimum value is pointless and increases the capital cost of the heat exchanger. The preliminary design involves selection of appropriate NTU and capacity rate ratio for the heat exchanger. From the capacity rate ratio and NTU, it is fairly straight forward to extrapolate the detailed design for the heat exchanger. A cooling system model was developed for the design process and for the simulation of the cooling system.